(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article presents a statistical analysis of the distribution of income indicators of the population of the Namangan region. The distribution of population income and the degree of social stratification were studied based on the Gini and Lorenz indices. A comprehensive empirical analysis of time series of population income indicators was carried out, descriptive statistics were determined, the normal distribution of the series was tested using the Jarque-Bera test, and stationarity was tested using the autocorrelation function and the Dickey-Fuller test. An AR model was constructed using data from 2014-2025 to forecast population incomes.